Estrategia de enseñanza virtual para el aprendizaje en línea de la asignatura emprendimiento y gestión en el bachillerato - Acosta Vergara, Carlos Andres (2022)
The COVID-19 pandemic has caused a change in the educational environment, it went from being face-to-face to virtual, it is necessary to think about didactic strategies for subjects that need a different treatment in their development and explanation. The objective of this article is to propose a virtual teaching strategy for the strengthening of online learning of the subject Entrepreneurship and Management in the baccalaureate. The research conducted is of hermeneutic approach and descriptive-explanatory scope. The selected sample is 58 students of the third year of high school of the Unidad Educativa Fiscal Durán, an intentional probabilistic sampling by quotas was applied, which facilitated the interpretation of results on the lack of use of virtual learning environments and technological tools by students and teachers. In addition, educators presented difficulties in the planning, development and evaluation of online classes. A virtual teaching strategy was designed to generate interaction and reflection in the teaching-learning process from the virtual environment, which has the following phases: virtual teaching-learning planning, communication and virtual teaching-learning activity, and online evaluation of assimilated learning.